Linguistic Creativity in Digital Marketing: A Sociolinguistic Analysis of Paronomasia in Emina Cosmetics’ Instagram Advertisements (PANOPTICON: Journal of English Studies, 2025)
This study investigates the use of paronomasia, or wordplay, in the product names and advertising captions of Emina Cosmetics on Instagram. Drawing from Delabastita’s (1996) typology of puns—homonyms, homophones, homographs, and paronyms—the research aims to identify the types and functions of paronomasia employed in Emina’s marketing strategies. Using a qualitative descriptive method, 21 Instagram posts from March 2015 to July 2024 were selected through purposive sampling. The analysis reveals that Emina Cosmetics utilizes various forms of paronomasia not only to attract attention and entertain audiences but also to build brand identity, enhance memorability, and subtly persuade consumers. The findings demonstrate that humorous and aesthetic language styles are prevalent, often blending Indonesian and English wordplay to appeal to a youthful, bilingual audience. This linguistic creativity reflects sociolinguistic trends in digital advertising, where informal, playful language contributes to engagement and emotional resonance. The study contributes to discourse analysis by highlighting how brands leverage linguistic devices to construct meaning and influence consumer perception. It also suggests practical implications for content creators and marketers seeking to integrate linguistic innovation into brand communication. Further research is encouraged to explore cross-cultural variations in pun-based advertising and its reception across different demographic segments